Pengaruh Suhu dan Lama Ekstraksi dengan cara Maserasi terhadap Karakteristik Pewarna dari Ekstrak Alga Merah (Gracilaria sp.) - Purba, Novia Esterulina; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): DesemberDO - 10.24843/JRMA.2019.v07.i04.p01, 2019)
Red algae (Rhodophyta) contains vitamins, minerals, fiber, sodium, potassium and bioactive compounds in the form of secondary metabolites and the most important nutrients are pigments.This study aims to determine the effect of temperature and length of extraction by maceration on the characteristics of dyes from red algae extract (Gracilaria sp.) spand determine the best temperature and maceration time to produce the color extract of Gracilaria sp. This study used Factorial Randomized Block Design. The first factor is temperature which consists of 3 levels namely 30±1°C, 40±1°C, 50±1°C. The second factor is maceration length which consists of 3 levels, namely 24 hours, 30 hours and 36 hours. Each treatment was grouped into 2 based on the time of implementation so that 18 units of experiment were obtained. The variables observed were yield, phycoeritrin, color intensity and effectiveness test. The data obtained were then analyzed by variance analysis and test Tukey’s. The results showed that the treatment of temperature, maceration time and interactions between treatments had a very significant effect on yield, phycoerythrin, brightness (L*), redness level (a*) and yellowness level (b*). The temperature of 30±1°C and the maceration time of 30 hours is the best treatment to produce dyes from red algae extract (Gracilaria sp.) with the characteristics of yield 0.496 ± 0.001%, phycoerythrin 0.430 ± 0.006 mg/g, lightness (L*) 20.470 ± 0.141, redness level (a*) 21.790 ± 0.198 and yellowish level (b*) 12.205 ± 0.035. Keywords: temperature, length of maceration, color, phycoeritrin, Gracilaria sp.